2020
DOI: 10.1186/s12909-020-02274-3
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of burnout in medical students using the Maslach Burnout Inventory-Student Survey: a cross-sectional data analysis

Abstract: Background Medical student burnout can cause emotional and physical exhaustion and detachment. The objectives of this study were to evaluate burnout using the Maslach Burnout Inventory-Student Survey (MBI-SS), identify factors that may predict burnout, and assess wellness initiatives effectiveness at reducing burnout. Methods The MBI-SS was administered to all medical students (Classes 2019 to 2022) at the University of Illinois Coll… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 44 publications
(54 reference statements)
7
39
0
6
Order By: Relevance
“…This correlates with prior studies that showed a higher degree of burnout in senior medical students. 16 , 17 The transition from preclinical years to clinical years of training appears to be a risk factor for academic stress in medical school. 5 , 24 The low burnout prevalence of fifth years may be due to them having learned some coping strategies such as life coaching, reflective practice, self-care, musical and physical activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This correlates with prior studies that showed a higher degree of burnout in senior medical students. 16 , 17 The transition from preclinical years to clinical years of training appears to be a risk factor for academic stress in medical school. 5 , 24 The low burnout prevalence of fifth years may be due to them having learned some coping strategies such as life coaching, reflective practice, self-care, musical and physical activities.…”
Section: Discussionmentioning
confidence: 99%
“…Burnout was assessed using the Maslach Burnout Inventory – Student Survey tool which was adapted from 17 , 18 and had been validated in Brazil. 19 The MBS-SS is a self-administered tool consisting of 15 questions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, notice that some authors have questioned the validity of the MBI to assess the burnout syndrome in medical student [ 22 , 25 ]. However, there are many authors who support its validity [ 26 28 ] and Dyrbye et al considered MBI as “the reference standard for measuring symptoms of burnout” [ 29 ]. In fact, MBI is the most applied tool in the worldwide to test this syndrome, being used in more than 90% of all empirical studies [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…It also negatively impacts decision making ability, relation-ships with colleagues and doctor patient relationship [8] .…”
Section: It Characterized By Emotional Exhaustion [Ee] Cynicism [Cy] and Low Academic Efficacy [Ae]mentioning
confidence: 99%